Do Immature Defense Mechanisms Mediate the Relationship Between Shame, Guilt, and Psychopathological Symptoms? - Cavalera, Cesare; Andreani, Paolo; Baumgartner, Oliver; Oasi, Osmano (Frontiers in Psychology, 2022)
Exploring the association between state-shame and state-guilt related to past stressful experiences and psychopathological symptoms and evaluating a mediation role by immature defenses. A total of 90 participants were considered in the present study to a) investigate correlations between state guilt and shame scores related to personal stressful events and psychopathological symptoms related to global severity index; b) assess correlations between state guilt and shame scores related to personal stressful events are positively correlated with immature defenses; c) test whether immature defenses mediates the relationship between respectively state-shame and state-guilt with psychopathological symptoms. Significant correlation between state-shame, state-guilt, psychopathological symptoms and immature defenses were found. Higher activations on immature defenses partially mediated the relationship between respectively state-shame and state-guilt and psychopathological symptoms. Past experiences related to shame and guilt should be targeted by specific treatments that could help stop recursive maladaptive thoughts and empower more adaptive defensive strategies.